2016
DOI: 10.1016/j.jamda.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Contributory Factors to Caregiver Burden in Parkinson Disease

Abstract: In PD, the CB is primarily dependent on patients' nonmotor symptoms. Patient care requires considerable time investment and can trigger depression in the caregiver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1
21

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 61 publications
7
75
1
21
Order By: Relevance
“…Sexual and relationship dissatisfaction among patients with PD paralleled that of their partners . The burden and increased depression in the caregiving partner can explain the sexual deterioration reported among spouses and partners of patients with PD …”
Section: Why Should Neurologists Talk About Sex With Their Parkinsonimentioning
confidence: 93%
See 2 more Smart Citations
“…Sexual and relationship dissatisfaction among patients with PD paralleled that of their partners . The burden and increased depression in the caregiving partner can explain the sexual deterioration reported among spouses and partners of patients with PD …”
Section: Why Should Neurologists Talk About Sex With Their Parkinsonimentioning
confidence: 93%
“…The most frequent SPB is sexual desire discrepancy (SDD), and the frequent demands for sex by patients, mainly men, negatively impact their partners . SDD can be created by adverse desire changes, including (1) Restored desire after the initiation of antiparkinsonian therapy with dopaminergic agents in patients and (2) decreased desire in the partner associated with burden and depression …”
Section: Why Should Neurologists Talk About Sex With Their Parkinsonimentioning
confidence: 99%
See 1 more Smart Citation
“…The nature and symptoms associated with PD can place significant stress on the caregivers' burden. As the prevalence of PD is estimated to more than double by 2030 [6], it is important to recognize and alleviate the burden experienced by caregivers [7]. …”
Section: Introductionmentioning
confidence: 99%
“…The paucity of research on the impact of off periods on carepartners is an important identified gap. Carepartners play a critical role in the care of patients, particularly as the disease progresses, but this role is associated with risk of strain and implications for the caregiver's own health . The limited data suggesting that off periods increase the patient's need for physical assistance and implications for activities outside the home are consistent with a study showing that psychosocial challenges for carepartners of patients include losing valued activities, feeling housebound, and being unable to predict the patient's daily well‐being.…”
Section: Discussionmentioning
confidence: 58%